2021
DOI: 10.1186/s12913-021-06365-9
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and perceptions of referrals to a community-based physical activity program for cancer survivors: a qualitative exploration

Abstract: Background Physical activity rates in cancer survivors continue to be low despite the known benefits and availability of evidence-based programs. LIVESTRONG at the Y is a national community-based physical activity program offered cost-free to cancer survivors, though is underutilized. We explored perceptions and experiences of staff and participating survivors to better understand program awareness, referrals and participation. Methods LIVESTRONG a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…This study adds to the growing body of studies evaluating health and fitness professionals’ perspective on the challenges and opportunities for exercise programming in cancer populations because previous studies have primarily focused on patient and care provider perspectives in understanding barriers and enablers to cancer exercise programming. Based on findings of prior research among cancer survivors (13–15,20), the responses obtained in the present study reinforce that cancer survivors and health and fitness professionals cite many similar perceived barriers such as education/awareness, referral/access, and cost (16,17).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…This study adds to the growing body of studies evaluating health and fitness professionals’ perspective on the challenges and opportunities for exercise programming in cancer populations because previous studies have primarily focused on patient and care provider perspectives in understanding barriers and enablers to cancer exercise programming. Based on findings of prior research among cancer survivors (13–15,20), the responses obtained in the present study reinforce that cancer survivors and health and fitness professionals cite many similar perceived barriers such as education/awareness, referral/access, and cost (16,17).…”
Section: Discussionsupporting
confidence: 73%
“…The study observed multifaceted from health and fitness professionals regarding barriers and/or enablers to community-based cancer programming. The present findings also underscore previously established challenges and opportunities in developing community-based exercise programs for individuals across the cancer-control continuum (15)(16)(17).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…27,[29][30][31] In another recent study of LIVESTRONG at the YMCA, researchers found that personal experiences of those who participated in the program resonated with survivors and increased participation. 40 Promoting a sense of community among participants appears key to motivating cancer survivors to enroll and adhere to the program.…”
Section: Implications For Public Healthmentioning
confidence: 99%